The Benefit of Gratitude: Trait Gratitude Is Associated With Effective Economic Decision-Making in the Ultimatum Game - Park, Gewnhi; vanOyen-Witvliet, Charlotte; Barraza, Jorge A.; Marsh, Benjamin U. (Frontiers in Psychology, 2021)
The current research investigated the role of gratitude in economic decisions about offers that vary in fairness yet benefit both parties if accepted. Participants completed a trait/dispositional gratitude measure and then were randomly assigned to recall either an event that made them feel grateful (i.e., induced gratitude condition) or the events of a typical day (i.e., neutral condition). After the gratitude induction task, participants played the ultimatum game (UG), deciding whether to accept or reject fair offers (i.e., proposer: responder ratio $5:5) and unfair offers (i.e., proposer: responder ratios of $9:1, $8:2, or $7:3) from different proposers. Results showed that trait gratitude was positively correlated with respondents’ acceptance of unfair offers. However, experimentally induced momentary gratitude did not influence acceptance of unfair offers. The trait or disposition to be grateful involves the enduring capacity across different types of situations and benefactors to see the good that is present, even when that benefit is small. Accordingly, dispositional gratitude—but not momentarily induced gratitude—was associated with a greater propensity to accept even the small benefits within unfair offers which otherwise pose barriers to making the effective economic decision of accepting offers regardless of their relative size.